(untitled) (Quinto Sol, 2013)
This study of Arizu´s family and their enterprise´s activity, examines the strategies for the purchase of an important volume of vineyards. These were known as “the largest carpet of vineyards of the world” in Mendoza at the begining of the twentieth century. For this research we have taken the persons, the family and the social networks as units of analysis, resorting to the information of the books of the Arizu enterprise and to the notary´s registers since 1884, year of the arrival of the first member of the family, up to 1920. We believe that the importance of this study is the microhistory perspective that offers a new point of view of the winegrowing economy. It also allows us to valídate or discuss some of the versions concerning the shaping of the high winegrowing bourgeoisie and the role of inmigrants. Appart from this, it lets us know the strategies that made it posible for the Arizu´s to be in the third place of the provincial producers. Finally, this study gives us information about the relationship between social networks and economic success.